Mobile Spinal Schwannoma with a Completely Cystic Appearance - Hamabe, Fumiko (Am J Case Rep, 2019)
Patient: Female, 48 Final Diagnosis: Spinal schawnnoma Symptoms: Dysuria • leg pain Medication: — Clinical Procedure: — Specialty: Orthopedics and Traumatology OBJECTIVE: Challenging differential diagnosis BACKGROUND: Spinal schwannomas are benign tumors arising from Schwann cells. Although they have been well described, tumor movement in the spinal canal is an extremely rare finding, and entirely cystic spinal schwannomas have rarely been reported. This is the first report of a spinal schwannoma that simultaneously exhibited both these unusual features. CASE REPORT: A 48-year-old female presented with dysuria and right leg pain. Initial magnetic resonance imaging (MRI) revealed a well-delineated intradural cystic lesion at the level of L4–S1 vertebrae that was isointense with cerebrospinal fluid on both T1- and T2-weighted images. A follow-up MRI 6 months later showed that the tumor had moved to the level of L2–L4; it also revealed tortuous configuration of nerve roots of the cauda equina. The tumor was resected, and a diagnosis of schwannoma with extensive cystic degeneration was pathologically confirmed. CONCLUSIONS: Various possible mechanisms have been suggested for the mobility of extramedullary tumors. In the present case, MRI findings indicated the cause of the tumor movement might be attributed to the laxity of nerve roots. Besides, it is highly atypical for a schwannoma to present an entirely cystic appearance, and the combination of the 2 extraordinary features made preoperative diagnosis difficult. However, 16 out of 22 (73%) of previously reported mobile spinal tumors were schwannomas, so the differential diagnosis for a mobile spinal tumor should include schwannoma, even when the lesion seems entirely cystic on MRI. To minimize the risk of complications and additional surgical dissection, physicians should acknowledge that spinal tumors can migrate.